MENUJU SISTEM EKONOMI PANCASILA: REFORMASI ATAU REVOLUSI - Mubyarto, Mubyarto (Journal of Indonesian Economy and Business, 2004)
.... intellectuals are at their best when distant from politics and power... only whenintellectuals step back from governing institutions will they be able to speak truth topower.... Intellectuals, therefore had to conceive of themselves as cultural worker,responsible not solely for generating ideas but also for ensuring that those ideas wound upin the minds and arguments of a thoughtful audience and public. (K. Mattson, 2002: 9, 267)Universities are introduced, without the intellectual spirit. A bureaucracy is introducedwithout the rigid and widespread adherence to the principal of promotion by merit,efficiency, and a public service attitude. Parliamentary democracy is introduced withoutthe spirit of fair play, honest election, and a genuine commitment to principles. Thesciences are introduced without the spirit of enquiry. The incomplete nature of themodernisation process, the substance without the spirit, is the cause of prevailingbackwardness of the developing societies. (Alatas, 1977: 78-79).Keywords: economic reform, economic exploitation, social-economic justice